Association of perioperative red blood cell transfusion with postoperative venous thromboembolism in pediatric patients: A propensity score matched analysis. Issue 10 (12th July 2019) - Rothstein, David H.; Cairo, Sarah B.; Schaefer, Beverly A.; Lautz, Timothy B.
Abstract: Objective: To examine the association between perioperative red blood cell (RBC) transfusion and postoperative venous thromboembolism (VTE) in pediatric surgical patients. Methods: Retrospective cohort study using the National Surgical Quality Improvement Project Pediatric, a validated registry of 118 United States children's hospitals. Patients under 19 years of age undergoing a surgical procedure between 2012 and 2017 were included, with the main exposure being RBC transfusion in the perioperative period (48 hours prior to operation to 72 hours after operation). The primary 30‐day outcome of interest was a postoperative VTE requiring therapy. Risk‐adjusted odds ratios (aOR) were calculated using multiple logistic regression. Subgroup analyses were performed across multiple surgical specialties. Sensitivity analyses were performed after (a) imputation for missing variables and (b) propensity score matching. Results: During the study years, 482 867 pediatric patients (56.7% male; median age, 6 years [interquartile range, 1–12 years]) underwent an operation. Of these, 30 879 (6.4%) received at least one perioperative RBC transfusion. Postoperative VTE requiring therapy occurred in 618 patients (0.13%). After adjustment for multiple risk factors, perioperative RBC transfusion was associated with an increased risk of VTE (aOR 2.4; 95% CI, 1.9–3.0). The increased VTE risk persisted after imputation of missing demographic and clinical data as well as after 1:1 propensity score matching (29 811 matched pairs, aOR 2.2; 95% CI, 1.7–2.8). Conclusions: Perioperative RBC transfusion is associated with an increased, albeit still very low, risk of postoperative VTE in pediatric patients. Patients receiving blood in the perioperative period may benefit from additional monitoring or VTE prophylaxis.